Diurnal activity patterns and feeding ecology of the endemic geladas (Theropithecus gelada) in the Simien Mountains National Park, Ethiopia. (2nd September 2014) - Ejigu, Dessalegn; Bekele, Afework
Abstract: Diurnal activity patterns and feeding ecology of geladas ( Theropithecus gelada ) in Chenek, Simien Mountains National Park, were studied from January 2010 to April 2010. Data were gathered for 7 days per month starting from early in the morning to dusk. The study site (1805 ha) was divided into five blocks and a total of 397 individuals were counted using simultaneous census method. One band with 21 individuals was selected as a study group and scan sampling was used to study their diurnal activity patterns and feeding ecology. Geladas dedicated significantly more time to foraging than to other diurnal activities. They spent the majority of feeding time foraging on grass, and allocated little time to feeding on leaves, shoots, and flowers. Geladas of all age classes devoted the least time to resting, and spent similar amount of time moving. The study band was observed to interact with people, and to steal food from tourists and local people. Raising local people's awareness of geladas ecology and behavior might be a necessary component in the species' successful management and conservation.